2018
DOI: 10.12697/akut.2017.23.08
|View full text |Cite
|
Sign up to set email alerts
|

Microsoft Kinect-based differences in lower limb kinematics during modified timed up and go test phases between men with and without Parkinson’s disease

Abstract: The aim of the study was to analyse with Microsoft Kinect (Kinect) the differences in lower limb kinematics during sub-phases of modified Timed Up and Go test (modTUG) in men with Parkinson's disease (PD) compared to healthy age-matched male individuals. Eight men with mild-to-moderate PD (age 67.5±4.5 yrs) and eight healthy men (age 69.8±8.0 yrs) participated. Kinect along with KinectPsyManager (v1.0) and Matlab2016b software was used for data collection. Selected lower limb kinematics and gait speed (GS) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In particular, the Microsoft Kinect® v1 has been used to assess movements in PD subjects (Galna et al 2014), postural sway (Yeung et al 2014), and balance (Yang et al 2014); while the more recent Microsoft Kinect® v2 has been used to assess balance dysfunctions (Eltoukhy et al 2018), posture and postural stability (Clark et al 2015;Grooten et al 2018), postural sway (Mishra et al 2017), to assess upper limb functions (Cai et al 2019), to evaluate clinical motor functions (Otte et al 2016;Clark et al 2019) in different fields of application, and for rehabilitation purposes (Garcia-Agundez et al 2019). In the context of neurodegenerative and neurological diseases, Microsoft Kinect v2 has been successfully employed for several clinical evaluations: Time Up and Go test (TUG) (Kähär et al 2017;Tan et al 2019), automatic recognition of different categories of PD subjects (Rocha et al 2015;Dranca et al 2018), automatic classification of gait patterns and disorders (Li et al 2018), assessment of neurological rehabilitation (Knippenberg et al 2017), and assessment of postural stability and lower limb impairments .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the Microsoft Kinect® v1 has been used to assess movements in PD subjects (Galna et al 2014), postural sway (Yeung et al 2014), and balance (Yang et al 2014); while the more recent Microsoft Kinect® v2 has been used to assess balance dysfunctions (Eltoukhy et al 2018), posture and postural stability (Clark et al 2015;Grooten et al 2018), postural sway (Mishra et al 2017), to assess upper limb functions (Cai et al 2019), to evaluate clinical motor functions (Otte et al 2016;Clark et al 2019) in different fields of application, and for rehabilitation purposes (Garcia-Agundez et al 2019). In the context of neurodegenerative and neurological diseases, Microsoft Kinect v2 has been successfully employed for several clinical evaluations: Time Up and Go test (TUG) (Kähär et al 2017;Tan et al 2019), automatic recognition of different categories of PD subjects (Rocha et al 2015;Dranca et al 2018), automatic classification of gait patterns and disorders (Li et al 2018), assessment of neurological rehabilitation (Knippenberg et al 2017), and assessment of postural stability and lower limb impairments .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies have investigated the accuracy and effectiveness of Microsoft Kinect for the assessment of posture, gesture, lower limbs and gait performance in several pathological states, such as stroke, Parkinson's disease [26,[65][66][67][68][69][70] and other pathologies [71][72][73][74]. Different studies have reported its reliability for the assessment of spatiotemporal gait parameters (e.g., step length and gait speed) and kinematic variables (e.g., trunk angle) in healthy individuals, with results comparable to those of laboratorygrade systems [25,[75][76][77][78][79][80] using both the first and second model of the device.…”
Section: Introductionmentioning
confidence: 99%
“…The Microsoft Kinect v2 is more robust and accurate as compared to Microsoft Kinect v1 [ 25 ], and it has been recognized a viable tool for tracking human movement in clinical applications [ 26 ], standing balance and postural stability [ 27 ], gait [ 28 ], body sway [ 29 ] and clinical motor functions [ 30 ]. In the specific context of neuro-degenerative diseases, it has been used for time up and go test [ 31 ], in assessing different types of PD patients [ 32 ], to classify gait disorders [ 33 ] and in neurological rehabilitation [ 34 ].…”
Section: Introductionmentioning
confidence: 99%